Text Coherence Necessary for the Promotion of Japanese EFL Learner’s Predictive Inference Generation - Masahiro MAEDA (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
Reading is a very complex process consisting of lower- and higher-level processing. Inference generation is necessary to achieve higher-level processing. It is challenging for Japanese EFL readers because they must use many cognitive resources in lower-level processing, such as word recognition and syntax analysis. This study investigated the relationship between Japanese EFL learners' predictive inference generation as higher-level processing and text coherence from the encoding perspective rather than activation. We used a cued recall task whose rates would be evidence of the reader's encoding of predictive inferences. The recall rates in the high predictability target version, which allowed readers to predict an outcome easily, were more significant than other text versions, and results were affected by the reader's proficiency. These findings suggest that EFL learners' encoding of predictive inference can be influenced under the specific text conditions in higher-level proficiency groups.